The Management of Erythrodermic Psoriasis Complicated by Cyclosporine. (8th September 2020) - Rao, Suman; Bernshteyn, Michelle; Sohal, Raman; Proumen, Rachael; Goodman, Alexandra; Shepherd, Zachary
Abstract : We present a 64-year-old woman with past medical history of psoriasis and alcoholic liver cirrhosis who presented with a diffuse, erythematous, and scaly rash. Pertinent medications included topical triamcinolone 0.1% cream. She was started on oral prednisone 40 milligrams (mg) and oral cyclosporine 150 mg daily and was continued on topical triamcinolone. After the administration of two doses of this regimen, the serum creatinine increased to 1.76 mg/dL, and serum potassium increased to 6.7 mEq/L. The serum creatinine continued to uptrend to 2.42 mg/dL, and the glomerular filtration rate (GFR) decreased to 20 mL/min. The patient was emergently hemodialyzed. The patient was placed on an extended steroid taper, alleviating the psoriatic rash. However, the patient needed to be placed on a steroid-sparing regimen. Because of its rarity and ensuing complications, erythrodermic psoriasis must be identified and managed promptly. Cyclosporine is currently the first-line treatment. However, initiation of this therapy in our patient resulted in an acute kidney injury (AKI). Even though a steroid taper assisted in alleviating erythroderma, a steroid-sparing regimen needed to be started. This led to the consideration of alternate methods of therapy for further management of erythrodermic psoriasis with renal impairment.